Defining the inflammatory signature of human lung explant tissue in the presence and absence of glucocorticoid - Rimington, Tracy L.; Hodge, Emily; Billington, Charlotte K.; Bhaker, Sangita; K C, Binaya; Kilty, Iain; Jelinsky, Scott; Hall, Ian P.; Sayers, Ian (F1000Research, 2017)
Background: Airway inflammation is a feature of many respiratory diseases and there is a need for newer, more effective anti-inflammatory compounds. The aim of this study was to develop an ex vivo human lung explant model which can be used to help study the mechanisms underlying inflammatory responses and which can provide a tool to aid drug discovery for inflammatory respiratory diseases such as asthma and COPD. Method: Parenchymal lung tissue from 6 individual donors was dissected and cultured with two pro-inflammatory stimuli, lipopolysaccharide (LPS) (1 µg/ml) and interleukin-1 beta (IL-1β) (10 ng/ml) in the presence or absence of dexamethasone (1 µM). Inflammatory responses were assessed using Luminex analysis of tissue culture supernatants to measure levels of 21 chemokines, growth factors and cytokines. Results: A robust and reproducible inflammatory signal was detected across all donors for 12 of the analytes measured following LPS stimulation with a modest fold increase (<2-fold) in levels of CCL22, IL-4, and IL-2; increases of 2-4-fold in levels of CXCL8, VEGF and IL-6 and increases >4-fold in CCL3, CCL4, GM-CSF, IL-10, TNF-α and IL-1β. The inflammatory signal induced by IL-1β stimulation was less than that observed with LPS but resulted in elevated levels of 7 analytes (CXCL8, CCL3, CCL4, GM-CSF, IL-6, IL-10 and TNF-α). The inflammatory responses induced by both stimulations was supressed by dexamethasone for the majority of analytes. Conclusions: These data provide proof of concept that this ex vivo human lung explant model is responsive to inflammatory signals and could be used to investigate the anti-inflammatory effects of existing and novel compounds. In addition this model could be used to help define the mechanisms and pathways involved in development of inflammatory airway disease.